Pengembangan Tortila Berkalsium Sebagai Alternatif Pangan Diet Casein Free-Gluten Free pada Industri Kecil dengan Metode Value Engineering - Jeremy Yonathan Sadikin; Agustinus Suryandono; Jumeri Jumeri (agriTECH, 2015)
The number of people with autism increased 56% in 1998 – 2013, and it was a global problem. People with autism need special treatments and CFGF diet (casein free, gluten free) was one of those treatments. That’s why, the development The calcium content was expected to substitute the calcium from dairy consumption, which shouldn’t be consumed by people with autism. The method used in this product development was value engineering which separated in three steps: information, creativity, and analysis steps. Respectively, this research was also further completed with chemical The goal of this research was to design some product implemented in small scale industry. Respondends and panelist in this research were consisted of students and teachers. They acted as the market of the product, especially as a  part of general society. This product were designed to provide CFGF snack for people with autism, and those who need CFGF diet. But this product was not limited to that market, it can be consumed by general society not only for people with autism, hence the students and teachers were used. The research showed that the best concept was a product produced with to get 200 grams of dough. This product concept was also designed to be packed in big size gusset packaging materials and the chips was triangle-shaped with size of feasible to be produced in small scale industry.ABSTRAKDengan jumlah penyandang autis yang terus meningkat, misalnya peningkatan sebesar 56% pada 1998 – 2013, maka produk tortila berkalsium potensial dikembangkan sebagai alternatif pangan untuk diet CFGF (casein free, gluten free) dan kandungan kalsiumnya bisa membantu menggantikan kalsium dari susu sapi yang mengandung kasein. Tujuan penelitian adalah merancang sejumlah konsep produk tortila berkalsium dan memilih satu konsep yang paling disukai Metode penelitian adalah yang terdiri dari tiga tahap: informasi, kreativitas dan analisa. Penelitian juga dilengkapi analisa lanjutan: analisa kimia guru, selaku masyarakat umum yang bisa mengonsumsi produk. Produk ini memang diawali dari adanya kebutuhan diet CFGF, namun konsumsi produk tetap bisa untuk umum sehingga produk bisa dikonsumsi semua kalangan, tidak terbatas hanya untuk penyandang autis yang perlu diet CFGF. Konsep terbaik yang diperoleh adalah tortila dengan komposisi bahan berupa rasio tepung jagung : tapioka sebesar 50:50 dan 3 g garam serta 7 g tepung tulang rawan ayampedaging, per 200 g adonan keripik. Konsep ini didesain dengan kemasan gusset ukuran besar, serta bentuk kepingan.